Light reduction and the electroretinogram of preterm infants. Issue 3 (1st May 1997) - Kennedy, Kathleen A; Ipson, Merle A; Birch, David G; Tyson, Jon E; Anderson, Jane L; Nusinowitz, Steven; West, Linda; Spencer, Rand; Birch, Eileen E
Abstract : AIMS: To examine the effects of light on retinal development and function in preterm infants as measured by the electroretinogram (ERG). Secondary outcomes included visual acuity testing, the incidence of retinopathy of prematurity, and general wellbeing, reflected in feeding tolerance, rate of weight gain, and length of hospital stay. METHODS: Eligibility criteria for enrolment were birthweight ⩽ 1250 g and gestational age ⩽ 31 weeks. Sixty one infants were randomly allocated by 6 hours after birth to a control or treatment group which wore 97% light filtering goggles for a minimum of four weeks or until the infant reached 31 weeks postmenstrual age. RESULTS: There were no significant differences between the two groups in the numbers of electroretinograms performed at 36 weeks of postmenstrual age. Although the sample size was not large enough to exclude clinically important differences in secondary outcomes, no significant differences were observed between the groups in visual acuity testing at 4-6 months corrected age, incidence of retinopathy of prematurity, weight gain, or length of stay. CONCLUSION: These data support the safety and feasibility of this intervention. A much larger study will be needed to determine whether light reduction to the eyes of very low birthweight infants will reduce the incidence of retinopathy of prematurity or enhance general wellbeing.